SOCIAL LIFE OF APPALACHIAN ENGLISHES - Cramer, Jennifer. ([S.l.])
1 online resource
Keywords: Appalachian Englishes (AEs) possess an array of linguistic features that distinguish them from other American Englishes, yet the rich history of language in the United States has created a wealth of linguistic resources through factors such as immigration and contact, providing the environment for AEs to grow and adapt in ways that are also similar to other varieties of English. AEs have a long history of representation in linguistic literature, but until now no single work has examined the interplay of language production and perception with an eye toward the role that language plays in the construction of personal and social identities. The Social Life of Appalachian Englishes takes a sociolinguistic/sociocultural approach to exploring specific linguistic features highlighted in the Linguistic Atlas Projects and the social life of Appalachian varieties in terms of perceptions and use. Focusing on the single theme of the social life of language in Appalachia, the book aims to explore the implications of the kinds of variation found, reinforce the notion that social meaning and variation are inseparable, and illustrate how linguistic production and perception are interrelated. It uses new data to amplify this theme, presenting a novel combination of data from different sociolinguistic traditions (specifically, perceptual dialectology and traditional atlas-style dialectology). Opportunities for engagement are provided through QR codes linking to additional resources and discussion questions and exercises at the end of each chapter. This book is designed for students and researchers interested in general linguistics, sociolinguistics, American Englishes, language variation, linguistic anthropology, and Appalachian studies.